Dynamic drape behaviours of wool woven suiting fabrics considering real-time use. Issue 5 (18th June 2021) - Balci Kilic, Gonca; Demir, Murat; Kilic, Musa
Abstract : Purpose: The purpose of this paper is to analyse dynamic drape behaviours of 100% wool woven suiting fabrics considering real-time usage. Design/methodology/approach: Dynamic drape coefficients of 100% wool woven fabrics were measured at different rotation speeds (25, 75, 125 and 175 rpm) with a commercially used fabric drape tester which works on image processing principle. Average daily walking speed of male and female volunteers was determined and the closest rotation speed was selected to calculate dynamic drape coefficient at walking ( DDCw ). Besides, bending rigidity and shear deformation properties, which are known to be related to the static drape behaviours of the fabrics, were also measured and the relationships between these parameters and DDCw were examined. Findings: As a result of the experimental study, it was found that dynamic drape coefficients become greater, which means the fabrics take flatter position, with the increase of the rotation speed. In addition, it was also seen that parameters known to be related to static drape behaviours such as unit weight and bending stiffness have less effect on the dynamic drapes of fabrics. For the estimation of dynamic drape behaviour of fabrics, parameters such as static perimeter, dynamic perimeter, etc. are found more significant. Originality/value: To date, although studies about dynamic drape behaviours of the fabrics claimed that dynamic drape gives more realistic results for in wearer experience, few of them focused on the rotation speed of dynamic drape tester for real-time usage. As dynamic drape behaviours of fabrics may differ for different rotation speed, determining appropriate speed in accordance with real-time usage gives more realistic results.